Enfoques de aprendizaje en estudiantes argentinos de nivel secundario y universitario (2021)
Learning approaches describe how students perceive and learn academic content. The local university system records high rates of student failure and dropout at the beginning of the academic year. For this reason, the learning of the high school and college students is analyzed. The TwoFactor Study Process Questionnaire was applied to 797 students (44% high school; 56% college students). First, the internal structure, was analyzed in samples of high school and college students. Then a MANCOVA found multivariate effects of the variables sex, educational level and the interaction between sex and educational level, on learning approaches. It is concluded that the questionnaire presents adequate psychometric properties in both groups of students. Besides, differencesin approaches were observed between high school and college students.Educational activities aimed at improving academic results during thetransition period, can be planned.